2019
DOI: 10.1021/acs.iecr.8b05474
|View full text |Cite
|
Sign up to set email alerts
|

Mutual Tailored Bimetallic Rh–Co Supported on La Modified SiO2 for Direct Ethanol Synthesis from Syngas

Abstract: In this work, Rh–Co/La2O3–SiO2 showed excellent selectivity to ethanol for direct ethanol synthesis from syngas. The best catalyst exhibited 42.8% selectivity to ethanol with CO conversion of 12.3% and in 145 h’ running maintained stable at 553 K, 3 MPa and GHSV of 3900 mL (gcat h)−1. The investigate results indicated that the interaction of cobalt denoting electron to rhodium adjusted the amounts of carbon monoxide adsorbed associatively and dissociatively, and maybe created a new active site pair of Rh0/Coδ+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 59 publications
(128 reference statements)
1
20
0
Order By: Relevance
“…37,39,40 The CO adsorbed associatively on the sites of cobalt or nickel would be hydrogenated to generate methanol, while the CO adsorbed dissociatively would be hydrogenated to generate CH 4 or other hydrocarbons, and the cooperation of the associative adsorption sites with dissociative adsorption sites would produce ethanol. 11,16,37,39,40 As shown in Figure 6a, for the monometallic Ni catalyst, Peak II′ was too small to be detected, and Peak II was attributed to the desorption of CO adsorbed associatively on nickel. For the monometallic Co catalyst, the peak located around 530 °C, considering the high desorption temperature, which should be attributed to the desorption of CO adsorbed dissociatively on metallic Co. With regard to the three bimetallic catalysts, the CO desorption profiles were similar, and both exhibited two desorption peaks corresponding to chemisorbed CO, where Peak II was attributed to the desorption of CO adsorbed associatively on Co δ+ /Co 2 C and Peak II′ was attributed to the desorption of CO adsorbed dissociatively on Ni.…”
Section: H 2 -Tprmentioning
confidence: 99%
See 3 more Smart Citations
“…37,39,40 The CO adsorbed associatively on the sites of cobalt or nickel would be hydrogenated to generate methanol, while the CO adsorbed dissociatively would be hydrogenated to generate CH 4 or other hydrocarbons, and the cooperation of the associative adsorption sites with dissociative adsorption sites would produce ethanol. 11,16,37,39,40 As shown in Figure 6a, for the monometallic Ni catalyst, Peak II′ was too small to be detected, and Peak II was attributed to the desorption of CO adsorbed associatively on nickel. For the monometallic Co catalyst, the peak located around 530 °C, considering the high desorption temperature, which should be attributed to the desorption of CO adsorbed dissociatively on metallic Co. With regard to the three bimetallic catalysts, the CO desorption profiles were similar, and both exhibited two desorption peaks corresponding to chemisorbed CO, where Peak II was attributed to the desorption of CO adsorbed associatively on Co δ+ /Co 2 C and Peak II′ was attributed to the desorption of CO adsorbed dissociatively on Ni.…”
Section: H 2 -Tprmentioning
confidence: 99%
“…The BEs of La 3d 5/2 for all the catalysts after reaction showed two peaks at 835.5 to 835.8 and 838.9 to 839.1 eV, which are close to that in La 2 O 2 CO 3 . 28,57 It is known that La 2 O 3 could react with CO 2 to form La 2 O 2 CO 3 during the reaction process, 16,27,58 which has a higher La 3d 5/2 BEs than pure La 2 O 3 . 59 The XPS results indicated that La 2 O 2 CO 3 was the main phase for La species in the used catalysts.…”
Section: H 2 -Tprmentioning
confidence: 99%
See 2 more Smart Citations
“…To overcome this challenge, considerable efforts have been exerted to stabilize Rh nanostructures against agglomeration by providing suitable support materials with large surface area. Traditional oxides, such as SiO 2 , Al 2 O 3 , and zeolite, or carbon materials such as graphene have been explored as supporting materials for Rh nanostructures.…”
Section: Introductionmentioning
confidence: 99%